1990
DOI: 10.1080/15324989009381245
|View full text |Cite
|
Sign up to set email alerts
|

Response of a shrub‐steppe ecosystem to fire: Soil water and vegetational change

Abstract: A wildfire in August 1984 eliminated big sagebrush from a shrub-steppe community in southeastern Washington. Bluebunch wheatgrass dominated the community in subsequent years. By comparing leaf area index and soil water storage on the burned site with an adjacent unburned site containing big sagebrush, we were able to test the hypotheses that plant community structure controls soil moisture dynamics and that wildfire can alter the water balance in these arid landscapes. Elimination of big sagebrush from the lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 16 publications
3
30
1
1
Order By: Relevance
“…Bromus tectorum rooting depth has been observed down to 80 cm in silt-loam soils (Cline et al 1977b) and 50 cm in sandy soils (Link et al 199Oa). More water will accumulate deep in the profile if shallowrooted plants, such as B. tecforum, dominate the surface than if deep-rooted plants dominate (Cline et al 1977b, Link et al 1990b, Gee et al 1992). …”
Section: Root Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bromus tectorum rooting depth has been observed down to 80 cm in silt-loam soils (Cline et al 1977b) and 50 cm in sandy soils (Link et al 199Oa). More water will accumulate deep in the profile if shallowrooted plants, such as B. tecforum, dominate the surface than if deep-rooted plants dominate (Cline et al 1977b, Link et al 1990b, Gee et al 1992). …”
Section: Root Functionmentioning
confidence: 99%
“…This is significantly less than the 15% volumetric soil water content found in the B. tectorum field . Variation in the rooting depth of deep-rooted perennials is associated with variation in soil water storage (Link et al 1990b). …”
Section: 10mentioning
confidence: 99%
“…LAI values for shrub-steppe communities are lower than those found in agricultural or forest ecosystems. LAI values for natural native bunchgrass communities found in finer soils on the Hanford site are roughly twice [0.11 to 0.13 LAI for communities that consist of small and large bunchgrasses and numerous forb species: see Link et al (1990)] the highest values represented here.…”
Section: Resultsmentioning
confidence: 89%
“…Figure C.5 shows the shrub leaf area variation throughout the year. Link et al (1990a) reported a maximum LAI value of 0.25 for sagebrush for 4 years in a sagebrush-bunchgrass community growing on a silt loam soil on the Fitzner/Eberhardt Arid Lands Ecology (ALE) Reserve. Our preliminary measurements at the proposed ILAW Disposal Site are showing similar LAI values.…”
Section: C12mentioning
confidence: 99%